Considering creativity : creativity, knowledge and practice in Bronze Age Europe - Sofaer, Joanna R. (Archaeopress Publishing Ltd, 2018)
The papers in this volume view Bronze Age objects through the lens of creativity in order to offer fresh insights into the interaction between people and the world, as well as the individual and cultural processes that lie behind creative expression.